Aripiprazole Treatment in a Patient with Schizophrenia and Severe Antipsychotic-Induced Parkinsonism Following Long-Term use of Methylphenidate: A Case Report. Issue 1 (1st March 2016) - Lee, Bong Ju
ABSTRACT: Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by various comorbid conditions including mood instability, personality problems, and addiction disorders, and ADHD-like features may also be an early vulnerability marker for schizophrenia. Because of these comorbidities, drug combination treatments and drug-drug interactions are becoming more important. Aripiprazole is an atypical antipsychotic medication with unique properties including dopamine D2 (D2) receptor partial agonism. The intrinsic activity of aripiprazole may serve as a basis for understanding why it can achieve a considerably higher degree of D2 receptor occupancy without causing the extrapyramidal side effects commonly seen with D2 receptor full antagonists and why clinicians may sometimes see aggravation of psychotic symptoms when they switch a patient from D2 full antagonists to aripiprazole. The present case report cautiously suggests the possible value of aripiprazole's stabilizing effects on the dopamine system in treating patients with schizophrenia who display severe antipsychotic-induced Parkinsonism after the cessation of methylphenidate used to treat attention deficit disorder.